The Effect of Acupuncture, Neuromuscular Taping, Tendon and Nerve Gliding Exercise on Improving Wrist Function in Conditions Carpal Tunnel SyndromeAt Clinic T - Handayani, Dwi Ratna S; Dheirani, Dheby; Rizki Amallia, Firdausiyah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Carpal Tunnel Syndrome (CTS) commonly affects workers with repetitive hand motions, causing pain, tingling, and impaired hand function due to median nerve compression. This study aimed to assess the effectiveness of combined tendon & nerve gliding exercises, neuromuscular taping, and acupuncture in reducing pain and improving wrist function in CTS patients. A quasi-experimental pre-post test design was applied to CTS patients aged 20-60 years at Binawan University, with interventions twice weekly for 3-4 weeks (gliding exercises 5-10 reps, taping 3-5 days, acupuncture at LI-4, PC-6, etc., 20-30 min/session). Assessments used VAS pain, BCTQ function, goniometer ROM, and MMT. Results revealed significant pain reduction (VAS from 4-5 to 1-2), improved ROM (dorsiflexion 10-20°), muscle strength gain (MMT up 1-2 grades), and BCTQ scores shifting from moderate to mild. The combination effectively reduced adhesions, enhanced nerve mobility, and promoted Qi circulation per TCM principles. In conclusion, this integrative approach is safe and effective for mild-moderate CTS, recommended as conservative therapy prior to surgery. Larger-scale studies are warranted.